Entering a foreign market: Exports, FDI or strategic alliance? - Karl Morasch (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2018)
The decision over exports vs. foreign direct investment (FDI) is usually discussed in an extension of the so-called Melitz model where firms with heterogeneous costs compete in a monopolistically competitive industry. The present paper starts from a situation where a potential foreign entrant would be just indifferent between exports and FDI in such a setting. However, by assuming oligopolistic interaction, strategic considerations are also taken into account. It is shown how the strategic impact of lower marginal cost makes FDI more attractive in a Cournot setting while exports are preferable under price competition in a market with differentiated goods. Beyond that it is also explored how a strategic alliance with a local incumbent could be a superior alternative for market entry.
Keywords: D43; L11; L41; 330; Entry strategies; Trade; FDI; Alliances; Oligopoly